Opciones para el desarrollo lechero en America tropical: Lecciones de Africa - Thorpe, W.R. (1998)
An account is given of the Development of dairy farming, milk production and stocking rate of cattle in Kenya, Gambia, Nigeria, Zimbabwe, Tanzania and Guinea-Bissau and the relevance of the African experience for sustainable small-scale agriculture in other tropical countries.